IMPLEMENTASI KEBIJAKAN PROGRAM BANK SAMPAH DI RW 07 KELURAHAN SUDAJAYA HILIR KOTA SUKABUMI - Agung Nugraha; Andriansyah Komarudin; Dzurotusshufiah Dzurotusshufiah; Fajar Satria Santana; Yuyu Yusinta; Neneng Yanti Andriani (Jurnal Pengabdian Kepada Masyarakat, 2023)
Waste management has become a critical issue in many countries, including Indonesia. The Bank Sampah program is one of the strategies used to manage waste effectively. This study aims to evaluate the implementation of the Bank Sampah program in RW 07, Sudajaya Hilir Village, Sukabumi City. This research uses a qualitative approach consisting of observation, interviews, and document analysis. The results showed that the Bank Sampah program in RW 07 had been implemented successfully, resulting in a decrease in the amount of waste sent to the landfill and an increase in community participation in waste management. However, several challenges still need to be addressed, such as improving the waste collection system and increasing public awareness of waste management. This study suggests the need for better coordination between the Bank Sampah program and the local government to ensure the program's sustainability.